(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Background. Diabetic retinopathy (DR) is one of the main complications of diabetes mellitus, the main cause of irreversible blindness in patients of working age in industrialized countries, has a high incidence rates and refers to neovascular eye diseases. At the present time, additional factors that affect the sensitivity to chronic hyperglycemia, the formation of microvascular complications, in particular, DR, include obesity and obesity-associated hormones of adipose tissue (adipokines: leptin, adiponectin, resistin, etc.). Purpose. To investigate the serum adiponectin levels in patients at different stages of DR in type 2 diabetes mellitus (T2DM) and obesity. Material and Methods. Study involved 99 patients, divided into 2 groups. The 1-st group (control group) consisted of 23 persons with obesity without T2DM (both male and female subjects; mean age, 57.03 ± 4.91 years), the 2-nd group consisted of 76 patients with T2DM, obesity and DR (both male and female subjects; mean age, 59.98 ± 4.17 years; mean duration of diabetes, 10.01 ± 2.81 years; mean glycated hemoglobin (HbA1C) level, 10.94 ± 2.08%), subdivided into 3 subgroups: with minimal and mild non-proliferative DR, with moderate to severe non-proliferative DR, with proliferative DR. The concentration of serum adiponectin was determined by ELISA kit. Statistical analysis included one- and two-factor analysis of variance. Results. Patients with mild non-proliferative DR had somewhat lower (worst) adiponectin levels among patients aged 60 and below with DM subcompensation. The lowest serum adiponectin levels were common for moderate to severe non-proliferative DR among T2DM patients aged above 60 with duration of diabetes of 10 years or less and with T2DM compensation. Among T2DM patients with proliferative DR, the worst serum adiponectin levels were common for T2DM patients aged 60 and below with duration of diabetes of less than 10 years and with T2DM compensation. Considering statistic values of serum adiponectin levels for this stage, it should be noted that, for conditionally combined proliferative DR with severe and moderate DR, statistically significant changes (р=0.007) consisted in the decreased serum adiponectin levels in T2DM compensation. Conclusions. Minimal and mild non-proliferative DR is characterized by a significant lower serum adiponectin level compared with the subsequent stages in subcompensation of T2DM.